Pengadaan Bak Sampah Sebagai Upaya Dalam Mengatasi Pencemaran Sungai Barito di Desa Malawaken - Zahra, Fatimatuz; Rifky, Haidar; Alfajri, Muhamad Alaihun; Nasrullah, Muhammad Pazri; Maimunah, Nurul Ayatul; Sarniwatie (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study discusses the program of providing trash bins as an effort to overcome pollution of the Barito River in Malawaken Village. The problem of waste polluting the river is mainly caused by the habit of local people to dispose of domestic waste and plastic carelessly. In the framework of the Real Work Lecture (KKN) program, three trash bins were procured which were placed in strategic locations, namely in the village government office, mosque, and prayer room. This program aims to increase public awareness in waste management and maintaining environmental cleanliness. The implementation of the program includes observation, preparation, implementation, and handover of trash bins. The results of this program are expected to increase community participation in maintaining the cleanliness of the river and its surrounding environment.